Scaling Scrum Across Modern Enterprises : Implement Scrum and Lean-Agile techniques across complex products, portfolios, and programs in large organizations /: Implement Scrum and Lean-Agile techniques across complex products, portfolios, and programs in large organizations. (2020) - Rupp, Cecil
No abstract available